Beating-heart robotic surgery using bilateral impedance control: Theory and experiments. (August 2018) - Sharifi, Mojtaba; Salarieh, Hassan; Behzadipour, Saeed; Tavakoli, Mahdi
Highlights: A force-based strategy is proposed for the teleoperation-assisted surgery of beating heart. Without any prediction or observation, compensation for the physiological heart motions is ensured. Oscillatory component of the beating-heart force is filtered out under the surgeon's hand. Two types of adaptation laws provide robustness against system uncertainties. Stability and tracking convergence are proven using the Lyapunov theorem. Abstract: A bilateral impedance controller is presented to enable robot-assisted surgery of a beating heart. For this purpose, two desired impedance models are designed and realized for the master and slave robots interacting with the operator (surgeon) and the environment (heart tissue), respectively. The impedance models are designed such that (a) the slave robot complies with the oscillatory motion of the beating heart and (b) the surgeon perceives the non-oscillatory portion of the slave/heart contact force at the master robot implying arrested-heart surgery. These performance goals are achieved via appropriate adjustment of the impedance model parameters without any measurement or estimation of heart motion. Two nonlinear robust adaptive controllers are proposed for the master and slave robots to track their corresponding desired impedance responses in the Cartesian space. The stability, tracking convergence and the robustness against parametric and non-parametric modeling uncertainties are proven using the Lyapunov theorem and based on two types of adaptation laws. The stability of impedance models and nonlinear tele-operation system can enhance the patient's safety during the robotic surgery. Experimental results show that the proposed controller compensates for the beating motion and provides smooth force feedback to the surgeon.